Upper limb kinematical analysis of an elite weight lifter in the squat snatch - Tang, G.; Qian, L.; Wang, D.; Wei, G.; Chang, D.; Wang, C.; Mi, W. (Computer Methods in Biomechanics and Biomedical Engineering, 2014)
The kinematical parameters such as translational acceleration and angular acceleration in the upper limb of a weightlifter may change regularly during different phases of squat snatch. This study aims to make this question clear. At first, the joint coordinate system (JCS) of human upper limb based on the anatomical landmarks is defined. Then a novel method for calculating the kinematical parameters was brought forward, which was based on analyzing the relative position of the JCS to world coordinate system during an instantaneous situation and the relationship among each JCS at different times during squat snatch. Motion capture system is used to gather the data of the upper limb in an elite weightlifter during squat snatch (the mass of the barbell is 20 kg) and the method mentioned before is applied to analyze the data. Finally, the law of the change of kinematical parameters in each phase of squat snatch is found.